THE INFLUENCE OF DATA-DRIVEN MARKETING ON PURCHASING DECISIONS AND CUSTOMER LOYALTY STUDIES AT BRAVO SUPERMARKET BOJONEGORO - Noor, Fauzian; Juwita, Agesti Martha; Agustino, Muhammad Rizqi (Distribusi - Journal of Management and Business, 2025)
This study investigates the impact of data-driven marketing on purchasing decisions and customer loyalty, focusing on a local retail context rarely explored in previous literature. Specifically, the research examines how the use of personalized marketing strategies based on customer data influences consumer behavior at Bravo Supermarket in Bojonegoro, Indonesia. Employing a quantitative approach with a cross-sectional survey design, the study collected data from a randomly selected sample of 100 customers using a structured questionnaire. The instrument measured customer perceptions of data-driven marketing strategies—such as personalized offers, targeted discounts, and purchase-based recommendations—as well as levels of satisfaction and loyalty. Empirical findings reveal a significant positive relationship between data-driven marketing and both purchasing decisions and customer loyalty. Customers responded favorably to marketing efforts tailored to their individual preferences and buying history, indicating that personalization enhances shopping experiences and encourages repeat purchases. Furthermore, loyalty programs like membership cards and reward systems, which are supported by customer data, were found to effectively strengthen long-term customer engagement. The results imply that even in regional retail settings, leveraging customer data can be a powerful tool for enhancing marketing effectiveness and building emotional connections with customers. This study contributes to the literature by providing localized insights into the practical benefits of data-driven marketing strategies in emerging markets.